Dose–response study of a fenugreek-based antibiotic alternative in Bábolna Tetra-SL chicks (1–42 days old) with mixed bacterial infections - Kerek, Ádám; Szabó, Ábel; Dobra, Péter Ferenc; Bárdos, Krisztina; Paszerbovics, Bettina; Bata, Zsófia; Molnár-Nagy, Viviána; Jerzsele, Ákos; Ózsvári, László (Frontiers in Veterinary Science, 2025)
IntroductionCombating antimicrobial resistance is one of the most pressing public health challenges of our time. The rapid spread of resistant, zoonotic bacterial strains in livestock farming is increasingly raising concerns about the need to reduce antibiotic use. Because of this, there is an urgent need for safe and effective alternatives in animal husbandry.MethodsThis study aimed to perform an in vivo the dose–response analysis of fenugreek (Trigonella foenum-graecum), as a plant-based antibiotic alternative feed supplement in Bábolna Tetra-SL chicks (1–42 days old) with a 1:1 sex ratio. A total of 270 chicks were randomly assigned to 18 groups (15 birds per group) and subjected to six different treatment groups in three replicates: fenugreek at 1×, 10×, and 100× doses, an antibiotic-treated group (enrofloxacin), a positive control group (infection only), and a negative control group (no infection or treatment). The infection was induced using mixed Salmonella Enteritidis and Escherichia coli, administered via gavage on days 3 and 4 of life. The birds were monitored for clinical symptoms, body weight, feed intake, and Salmonella shedding through cloacal swab samples. Statistical analyses included mixed-effect logistic regression for mortality, mixed-effect linear models for weight gain, two-way ANOVA for feed efficiency, and random effects continuation ratio models for Salmonella isolation.ResultsSignificant interactions for Group:Day and Sex:Day in weight gain were identified (p < 0.0001 for both). Additionally, the 1 × dose group showed significantly reduced Salmonella shedding compared to the positive control group on day 33 (p = 0.0031). The low-dose group (1×) demonstrated the most promising results, showing a 63% reduction in Salmonella shedding on day 10 and 31% on day 17. This group exhibited the fewest clinical symptoms, no diarrhea, and the lowest individual and specific feed intake up to day 24.DiscussionThe findings of this study suggest that low-dose fenugreek supplementation could be a viable strategy for reducing Salmonella shedding in poultry, potentially contributing to reduced antibiotic use in poultry farming and thus playing a role in the global effort to combat antimicrobial resistance. Future research will involve large-scale industrial trials and next-generation sequencing to evaluate the additive’s impact on gut microbiota composition.